6y-2=-3

Simple and best practice solution for 6y-2=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y-2=-3 equation:


Simplifying
6y + -2 = -3

Reorder the terms:
-2 + 6y = -3

Solving
-2 + 6y = -3

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 6y = -3 + 2

Combine like terms: -2 + 2 = 0
0 + 6y = -3 + 2
6y = -3 + 2

Combine like terms: -3 + 2 = -1
6y = -1

Divide each side by '6'.
y = -0.1666666667

Simplifying
y = -0.1666666667

See similar equations:

| 20y^2+9y-20=0 | | 04(1.5c+6)-2c=-9 | | x-20=60 | | 3x+6y+4z=2900 | | 7x-11=3x-3 | | 140=192-w | | -3x+6(2x+9)=9 | | 5x-34=17 | | x+10=400 | | 2x+3x+15=30 | | 3+2n= | | 125=-w+236 | | -2r+6(r-1)+3r-(4-r)=(r+5)-5 | | 4-7j=f-12 | | 1+1=8 | | -v+61=185 | | (7t-2)(-3t+1)=-3(1-3t) | | 22-6=4h | | 85+17x=-87+13x | | 11x-6=6x+14 | | 5(x+2)=3k-1 | | x+x+2+x+4+x+6=464 | | -5.9-(-4.9)= | | x+x+1+x+2=156 | | 102=9x | | -136+2x=6x+132 | | y=20+3x | | 9=3v+37+4v | | y=0.15x+2.94 | | 10x-6=5x+9 | | 0.4m+4=7.6 | | 10-4x-pix=0 |

Equations solver categories